Morphology of stomatopod larvae from National Parks: Sistema Arrecifal Veracruzano and Arrecife Puerto Morelos, Mexico - Cházaro-Olvera,Sergio (2018)
ABSTRACT The present study provides information on the morphology of stomatopod larvae found in two different reef systems which are also considered national parks: the Sistema Arrecifal Veracruzano (SAVNP) and Arrecife Puerto Morelos (APMNP). Zooplankton samples were collected at 26 stations of the SAVNP and four stations of the APMNP. Stomatopod larvae were identified and classified by their larval stage. We found representatives of three stomatopod superfamilies: the superfamily Gonodactyloidea Giesbrecht, 1910 was represented by Neogonodactylus oerstedii (Hansen, 1895), Neogonodactylus wennerae Manning and Heard, 1997, and Pseudosquillidae genus and species indeterminate; the superfamily Lysiosquilloidea Giesbrecht, 1910 was represented by Lysiosquilloidea genus and species indeterminate, Lysiosquilla sp., Lysiosquilla scabricauda (Lamarck, 1818) and Nannosquilla adkisoni Camp and Manning, 1982; the superfamily Squilloidea was represented by larvae of Alima neptuni (Linnaeus, 1768), Squilla spp., and Squilla empusa Say, 1818. We were able to identify and describe four stages of larval development for representatives of these superfamilies. This is the first study describing several stages of larval development of different species of the stomatopods from the Gulf of Mexico and Caribbean Sea.